Determination of the Toxic Dose of Experimental Lead Poisoning for Male Goats in Fallujah City, Iraq - Omar Fahad; Mawlood Al-Graibawi (مجلة الانبار للعلوم البيطرية)
This study aimed to induce lead poisoning experimentally in male goats to determine the toxic dose and investigate it is effects on hematological parameters, and the functions of the liver and kidney. The experiment was performed on 15 male goats, aged between 3 – 5 months with a mean weighing 13±0.65 kg. Goats were divided into five equal groups, the first represented the control group given tap water, while the other groups were given orally (by stomach tube) 70,100,200 and 400 mg/kg B.W. of lead acetate respectively, for 5 days. Blood was collected weekly for 4 weeks to estimate the concentrations of lead, hematological and biochemical analysis. The results indicated a significantly (P≤0.05) increase of lead(0.738±0.07ppm), only in goats which received 400 mg Pb/kg B.W of lead with symptoms included: depression, dullness, anemia, muscle twitching, staggering, and teeth grinding, with a significant reduction in erythrocyte count, packed cell volume, and hemoglobin 10.391±0.41*106/ml, 25.5±0.55%, and 8.30±0.19g/dl respectively, compared with the control ones. Also, increase in total white blood cell count to 9.098±0.08*103/ml, neutrophils 39.07±0.93%, monocytes 1.88±0.07%, and eosinophils 4.82±0.05%. The same group results showed significant elevations in the activities of liver enzymes; ALT 59.9±0.20u/l, AST 243±1.3u/l, in addition, the serum levels of creatinine and urea were also increased indicating renal frailer 1.96±0.05 mg/dl and 29.78±0.34 mg/dl respectively. In summary, this is the first study that proved the toxic dose of lead poisoning for male goats in Iraq and estimate their hazardous results on the hematological and chemobiological analyses on goats.